Comparison of internal organ injuries by blunt abdominal trauma in rats with empty or full stomach - Kafadar, Huseyin; Kafadar, Safiye; Tokdemir, Mehmet (Turkish Assoc Trauma Emergency Surgery, 2014)
BACKGROUND: The aim of the study was to investigate if there was a difference in injury in intra-abdominal viscera due to blunt abdominal trauma sustained by rats with empty or full stomach and to examine which viscera is affected most, based on the direction of the trauma. METHODS: Since there is no data in the literature on the force of trauma, a pilot study was carried out before commencing the experimental study. An apparatus was built to determine the trauma force that would not cause sudden death, and rats were allowed free fall from a height of 40 and 45 cm so that they would land on their abdomen. The most appropriate force of trauma (F=69.978 N) and absorbed energy (E=1/2mv(2)=0.979 Joules) were obtained in rats weighing 250 g that fell from a height of 40 cm. RESULTS: Thirty six rats were included in the study and separated into six groups. Any statistically significant differences between groups with regard to the stomach being empty or full during trauma and its direction were examined (anterior, right/left sided). CONCLUSION: It was observed that there were differences in injuries sustained by the internal organs depending on the fullness or emptiness of the stomach and the direction of the trauma.
Keywords: Blunt abdominal trauma; forensic medicine; rat; trauma